Direct observation of excitonic instability in Ta2NiSe5 - Kwangrae Kim (Nature Portfolio, 2021)
Concominant structural and electronic phase transitions in the excitonic insulator candidate Ta2NiSe5 make the identification of the driving mechanism of the transition challenging. Here, the authors report evidence for electronically-driven transition via Raman susceptibility measurements.